BANDUNG CLAY : PROPERTIES, STRUCTURE AND STABILITY AGAINST EMBANKMENT FAILURE - b. Setjadingrat, Carolus
Interest in the thick deposit of soft clay, formed in recent geological time in the Bandung lake area, increased when the Padalarang-Cileunyi Toll Highway was to be constructed on an alignment crossing the deposit. The clay has been found to show unusual behaviour, having very high moisture content and low density, but relatively good stability. The structure and the behaviour of the sails comprising the deposit were greatly influenced by the geological history of the site. The volcanic origin of the material and the tropical weathering processes have lead to the formation of halloysite and allophane clay minerals, with significant presence of diatomaceous silica in the deposit. This has resulted in a very open structured arrangement of the soil particles. As a result of the clay mineral types present, the plasticity of Bandung clay is very sensitive to the manner of testing, particularly to the amount of drying of test samples. The liquid limit and plastic limit values drop significantly when the clay is subjected to drying before testing. The stability analyses of embankments built over this deposit, using total strength and effective strength methods of analysis, have suggested that stability is not a problem for embankments with fill heights less than about 9 m. On the other hand, some means of reinforcement were indicated as being needed when the fill heights exceed 10 m, depending on the rate of construction, in order that an adequate minimum factor of safety on stability be maintained.